Could I, should I? Parenting aspirations and personal considerations of five young women with 22q11.2 deletion syndrome. Issue 4 (2nd October 2017) - Phillips, Lisa; Goodwin, Jane; Johnson, Martin P.; Campbell, Linda E.
ABSTRACT: Background This phenomenological study explores the perceptions, hopes, and dreams of relationships and parenting of women with a genetic intellectual disability. Method Five women with both 22q11.2 deletion syndrome (22q11DS) and intellectual disability took part in semistructured interviews. Their subjective interpretations were analysed using interpretative phenomenological analysis. Results Four main themes emerged: (a) challenges and acceptance of having 22q11DS, (b) desire for social acceptance and normality, (c) welcoming of emotional and practical support, and (d) individuation. The themes describe the discordance between the challenges and acceptance of having a genetic disorder, the need to be "normal, " the importance and appreciation of social support, and the women's aspirations for independence. Conclusions Young women with 22q11DS approach their adulthood with a sense of optimism and personal competence yet recognise their unique challenges. Parental support is valued despite the need for independence. The findings provide insight into the lived experience of women with 22q11DS.